2022
DOI: 10.3390/nu14224895
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosorus terminans Extract Ameliorates Insulin Resistance and Non-Alcoholic Fatty Liver Disease (NAFLD) in High-Fat Diet (HFD)-Induced Obese Rats

Abstract: Interruptins A and B exhibited anti-diabetic, anti-inflammatory, and anti-oxidative effects. This study aimed to investigate the therapeutic ability of extract enriched by interruptins A and B (EEI) from an edible fern Cyclosorus terminans on insulin resistance and non-alcoholic fatty liver disease (NAFLD) in a high-fat diet (HFD)-induced obese rats and elucidate their possible mechanisms. HFD-induced obese rats were treated with EEI for 2 weeks. Real-time polymerase chain reaction (PCR) was used to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Therefore, it cannot be excluded that GW9662 partially blocks PPARα, contributing to the reversion of the anti-steatotic effect of BCP observed in our experiments. In accordance with recently published results [ 40 ], we found that both PPARα and γ are downregulated during the pathological condition of steatosis. Intriguingly, co-treatment with BCP induced a marked upregulation of PPARα, bringing it back to even higher expression levels than in the untreated control.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it cannot be excluded that GW9662 partially blocks PPARα, contributing to the reversion of the anti-steatotic effect of BCP observed in our experiments. In accordance with recently published results [ 40 ], we found that both PPARα and γ are downregulated during the pathological condition of steatosis. Intriguingly, co-treatment with BCP induced a marked upregulation of PPARα, bringing it back to even higher expression levels than in the untreated control.…”
Section: Discussionsupporting
confidence: 93%
“…Several plant extracts, including those derived from Hibiscus sabdariffa, Panax notoginseng, Antidesma bunius, Curcuma longa Linn., Aralia elata, Cyclosorus terminans, Pluchea indica, and R. officinalis Linn. (Table IV), upregulated the expression leels of SREBP-1c, FAS, ACC, and CPT-1, as well as PPAR-α, a regulator of β-oxidation, in rats that were fed a HFD (83,84,94,95,101,105,109,114,115). This suggests that AMPK activation by these herbal compounds is associated with de novo lipid synthesis, which is linked to the suppression of SREBP-1c, PPAR-α, FAS, ACC and CPT-2 expression.…”
Section: Mechanism Of Actionsmentioning
confidence: 87%
“…The extracts of Antidesma bunius (82,83), Aralia elata (84)(85)(86), Citrus aurantium (90)(91)(92)(93), Curcuma longa Linn. (94)(95)(96), Cyclosorus terminans (101,102), Panax notoginseng (109), Pluchea indica (114), and Rosmarinus of f icinalis Linn (115,116) have also been shown to reduce the accumulation of lipids in rats fed a HFD through sterol regulatory element-binding transcription factor 1c (SREBP-1c), peroxisome proliferator-activated receptor-α (PPAR-α), fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC), and carnitine palmitoyltransferase (CPT)2 regulation. The adenosine monophosphate-activated protein kinase (AMPK) pathway plays a crucial role in regulating hepatic lipogenesis and β-oxidation and serves as a vital energy sensor for intracellular energy metabolism.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…A positive energy balance coming from a high energy intake promotes excessive accumulation of visceral fat and obesity-related comorbidities [ 44 , 45 ]. As expected, the H group showed obesity (↑body weight gain and ↑body fat accumulation by MRI), as reported in high-fat/high-fructose diet models [ 45 ]. Meanwhile, HBL prevented obesity (↓body fat accumulation by MRI without changes in body weight gain).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the H group developed obesity and dyslipidemia by increased total cholesterol, triglycerides, VLDL-c, and HDL-c, in addition to impaired glucose tolerance, compensatory hyperinsulinemia, and insulin resistance. These common metabolic alterations induced by high-fat/high-fructose models are strongly related to nonalcoholic liver disease development [ 45 ].…”
Section: Discussionmentioning
confidence: 99%